A survey on the status of BIV-infection and associated clinical findings in old- age Holstein cattle of some dairy farms aruond of Tabriz - mohammad tooloei; samad farrashi; hamed panahpour (Āsīb/shināsī-i Darmāngāhī-i Dāmpizishkī, 2013)
Bovine immunodeficiency virus is a Lentivirus from the large family of retroviridae. Different opinions have been submitted about the possibility of varieties of infectious complications due to Bovine immunodeficiency virus and induced losses to dairy industry. Considering the worldwide distribution of the BIV infection in cattle herds and correlation of the infection with different kinds of clinical disorders and consequent severe economic losses to dairy cattle industry and the fact that only few surveys about the status of the BIV infection have been performed in Iran as well as the probability of increasing infection rate with aging and therefore increasing the culling rate, this study was done to identify the BIV infection rate in aged Holstein cattle and evaluation of their associated clinical disorders in some dairy herds around Tabriz. In this study which was performed in some industrial or traditional especially the small dairy farms around Tabriz, 50 Holstein dairy cattle with the age of higher than 6 years old were selected and their clinical characteristics recorded. Blood samples were taken to detect BIV genome. According to the results of the Nested-PCR method in this study, 2% (1/50) of the aged cattle were infected with BIV. There wasn’t any significant correlation between BIV infection rate and age. Also there weren’t any significant correlations between BIV infection rate and BCS, milk production rate, any clinical problems, enlarged lymph nodes and haemal nodes. The results showed that the BIV infection rate among the aged cattle was relatively low and in contrast to some other studies, aging does not affect the sensitivity to infection. Decreasing the population in the livestock units and farms, could be helpful in prevention and control of BIV infection in cattle.